MINIMIZE WASTE MOTION IN THE PRODUCTION PROCESS LAYOUT - Fenza Gusti Naufal Paleva; Eka Bambang Gusminto; Fiona Niska Dinda Nadia; Ariwan Joko Nusbantoro; Rasyidi Faiz Akbar (Airlangga Development Journal, 2023)
This study aims to determine the factors that cause waste motion and provide a proposed improvement and improvement design to minimize the factors that cause waste motion in the production process of UD Putera Sroedji Jember. UD Putera Sroedji is a medium-scale company in the field of rice production in the Jember area. The problems found at UD Putera Sroedji are the production flow that is not suitable in general and the distance between departments is quite far. These two things are one of the causes of the company's waste motion. The data was obtained by making observations to observe the flow of the production process as well as measuring distance and time. Data analysis used ARC, ARD and Kaizen methods. The results show that the efficiency level given from the two production process lines, namely the proposed layout will be estimated to be able to reduce the production distance of line 1 along 31.25 meters or more efficiently by 30.65% with time savings of 2.828.75 seconds. 2 along 45.4 m or more efficient by 38.07% with a time saving of 3,980.15 seconds.